Aromatherapy Therapy Basics - McGuinness, Helen (London : Hodder & Stoughton, 1997)
This text on aromatherapy provides a much needed resource for students of aromatherapy courses, and its particularly aimed at NVQ level 3. The author covers the required underpinning knowledge and provides plenty of self-assessment questions.
Includes bibliographical references (p. 176) and index.
Keywords: Aromatherapy; Health and Fitness